Prevalence of Genetically Complex Leishmania Strains With Hybrid and Mito-Nuclear Discordance - Kato, Hirotomo; Cáceres, Abraham G.; Gomez, Eduardo A.; Tabbabi, Ahmed; Mizushima, Daiki; Yamamoto, Daisuke S.; Hashiguchi, Yoshihisa (Frontiers in Cellular and Infection Microbiology, 2021)
Approximately 20 Leishmania species are known to cause cutaneous, mucocutaneous, and visceral disorders in humans. Identification of the causative species in infected individuals is important for appropriate treatment and a favorable prognosis because infecting species are known to be the major determinant of clinical manifestations and may affect treatments for leishmaniasis. Although Leishmania species have been conventionally identified by multilocus enzyme electrophoresis, genetic analysis targeting kinetoplast and nuclear DNA (kDNA and nDNA, respectively) is now widely used for this purpose. Recently, we conducted countrywide epidemiological studies of leishmaniasis in Ecuador and Peru to reveal prevalent species using PCR-RFLP targeting nDNA, and identified unknown hybrid parasites in these countries together with species reported previously. Furthermore, comparative analyses of kDNA and nDNA revealed the distribution of parasites with mismatches between these genes, representing the first report of mito-nuclear discordance in protozoa. The prevalence of an unexpectedly high rate ( 10%) of genetically complex strains including hybrid strains, in conjunction with the observation of mito-nuclear discordance, suggests that genetic exchange may occur more frequently than previously thought in natural Leishmania populations. Hybrid Leishmania strains resulting from genetic exchanges are suggested to cause more severe clinical symptoms when compared with parental strains, and to have increased transmissibility by vectors of the parental parasite species. Therefore, it is important to clarify how such genetic exchange influences disease progression and transmissibility by sand flies in nature. In addition, our aim was to identify where and how the genetic exchange resulting in the formation of hybrid and mito-nuclear discordance occurs.